Resistance evaluation of Chinese wild Vitis genotypes against Botrytis cinerea and different responses of resistant and susceptible hosts to the infection - Wan, Ran; Hou, Xiaoqing; Wang, Xianhang; Qu, Jingwu; Singer, Stacy D.; Wang, Yuejin; Wang, Xiping (Frontiers in Plant Science, 2015)
The necrotrophic fungus Botrytis cinerea is a major threat to grapevine cultivation worldwide. A screen of 41 Vitis genotypes for leaf resistance to B. cinerea suggested species independent variation and revealed 18 resistant Chinese wild Vitis genotypes, while most investigated V. vinifera, or its hybrids, were susceptible. A particularly resistant Chinese wild Vitis, “Pingli-5” (V. sp. [Qinling grape]) and a very susceptible V. vinifera cultivar, “Red Globe” were selected for further study. Microscopic analysis demonstrated that B. cinerea growth was limited during early infection on “Pingli-5” before 24 h post-inoculation (hpi) but not on Red Globe. It was found that reactive oxygen species (ROS) and antioxidative system were associated with fungal growth. O2- accumulated similarly in B. cinerea 4 hpi on both Vitis genotypes. Lower levels of O2- (not H2O2) were detected 4 hpi and ROS (H2O2 and O2-) accumulation from 8 hpi onwards was also lower in “Pingli-5” leaves than in “Red Globe” leaves. B. cinerea triggered sustained ROS production in “Red Globe” but not in “Pingli-5” with subsequent infection progresses. Red Globe displayed little change in antioxidative activities in response to B. cinerea infection, instead, antioxidative activities were highly and timely elevated in resistant “Pingli-5” which correlated with its minimal ROS increases and its high resistance. These findings not only enhance our understanding of the resistance of Chinese wild Vitis species to B. cinerea, but also lay the foundation for breeding B. cinerea resistant grapes in the future.